Fatal harbor [large type] - DuBois, Brendan (DuBois, Brendan. Lewis Cole mystery., 2014)
Days after a violent anti-nuclear demonstration puts his best friend, police detective Diane Woods, in a near fatal coma, former Department of Defense analyst Lewis Cole abandons his job and home to find the man responsible. From rural New Hampshire to Washington D.C., he follows his gut and the flimsiest of clues. Suffering loss, heartache, and betrayal along the way, Cole is soon standing alone, facing his own ultimate test: how far will he go to avenge a friend?